PP.09.14: ADRENAL VENOUS SAMPLING. (June 2015) - Solar, M.; Ballon, M.; Krajina, A.; Lojik, M.; Raupach, J.; Ceral, J.
Abstract : Objective: Primary aldosteronism (PA) is a potentially curable form of secondary arterial hypertension provided there is unilateral aldosterone overproduction. Adrenal venous sampling (AVS) enables to identify the PA patients who can profit from unilateral adrenalectomy. The aim of the study was to analyse the AVS experience in our centre. Design and method: The data of the patients who were referred for AVS were enrolled in the study. All AVS procedures were performed according to the routine standardised protocol used in our centre. An infusion of cosyntrophin was administered 30 minutes before and during the procedure. Samples were taken step by step from both adrenal veins, and the inferior vena cava. Adrenal samples were considered adequate if the cortisol concentration was at least 5-fold greater than that of the inferior vena cava. The lateralization of aldosterone secretion was confirmed when cortisol-corrected aldosterone concentration from the affected gland was at least 4-fold higher than that of the contralateral side. The procedural success, the frequency of lateralisation of aldosterone secretion, and the complication rate were the main analysed parameters. Results: In the period 2005–2014, the AVS was performed in 184 patients. After repeating the procedure in 17 (9.2%), the adequate adrenal samples were obtained in 170 (92.4%) of patients. The lateralization of aldosterone secretion was identified in 72 (42.3%) cases where the AVS was successful. One periprocedural complication was noted. An adrenal hematoma developed as a consequence of adrenal vein injury. This adverse event resolved without a negative sequel. Conclusions: Provided the procedure is initially unsuccessful, repeating the AVS increases the success rate not augmenting the risk of complications. The rather high number of cases with proven lateralization of aldosterone secretion could be attributed to the selection of patients who have a high probability of surgically correctable form of PA when initiating the PA screening.